The only - Applegate, Katherine (Applegate, Katherine. Endling ;, 2021)
A trilogy conclusion finds Byx and her friends discovering that the same extinction facing the dairnes is threatening all living species, prompting the team to recruit creatures throughout the world into their revolution.